Implementation of Covid-19 on Character Education - Suwarno Suwarno; Durhan Durhan; Muhaimin Muhaimin (Syntax Corporation Indonesia, 2021)
Corona Virus Disease 2019 or known as COVID-19 outbreak was first discovered in Wuhan, China in December 2019 and then designated as a pandemic by WHO on March 11, 2020. This study uses the method of literature research or literature studies. To implement character education during the covid-19 pandemic, good cooperation between parents, educators (teachers), communities and governments (educational units) is needed to achieve success in character building.